Involvement of Genes on a Megaplasmid in the Acid-Tolerant Phenotype of Rhizobium leguminosarum Biovar Trifolii - Chen, Hancai (1993)
The acid-tolerant Rhizobium leguminosarum biovar trifolii strain ANU1173 exhibited several new phenotypes when cured of its symbiotic (Sym) plasmid and the second largest megaplasmid. Strain P22, which has lost these two plasmids, had reduced exopolysaccharide production and cell mobility on TY medium. The parent strain ANU1173 was able to grow easily in laboratory media at pH 4.5, whereas the derivative strain P22 was unable to grow in media at a pH of <4.7. The intracellular pH of strain ANU1173 was 6.8 when the external pH was 4.5. In contrast, strain P22 had an acidic intracellular pH of <6.4 when the external pH was <5.5. Strain P22 had a dramatically increased membrane permeability to protons and decreased proton extrusion activity. Analysis with sodium dodecyl sulfate-polyacrylamide gels showed that strain P22 lacked a slow-migrating lipopolysaccharide (LPS) banding group which was present in the parent strain. Mobilization of the second largest megaplasmid of strain ANU1173 back into strain P22 restored the altered LPS structure and physiological characteristics of strain P22. Mobilization of the Sym plasmid of strain ANU1173 into strain P22 showed that the second largest megaplasmid of strain ANU1173 was required for the establishment of nitrogen-fixing nodules on Trifolium repens and Trifolium subterraneum. Furthermore, an examination of a large number of specific exopolysaccharide- or LPS-deficient Rhizobium mutants did not show a positive correlation between exopolysaccharide or LPS synthesis and acid tolerance.